Oral lesions and disorders and their prevalence arising from the use of illicit drugs in a prison population. - Marta Relvas; Luciana Rocha; Paulo Rompante; Filomena Salazar; Luís Monteiro; Ana Sofia Vinhas; Maria Gonçalves (Acta Odontologica Scandinavica)
Background: The dependence on the illicit drugs has been proven to be harmful to the oral cavity and may lead to a series of abnormal manifestations. The main objective of this study was to observe the effects caused by the consumption of illicit drugs in the oral cavity, in a prison population in the North of Portugal.